(untitled) (Conferencea, 2024)
In order to maintain the volume of public procurement at an acceptable level, it is important to ensure its high efficiency. However, the public sector does not have the incentives to increase the efficiency of procurement that are inherent in the private sector. This situation is a factor that creates a higher risk of corruption than in other areas of the public service. Previously, this sector did not have transparency, free registration and participation in electronic auctions, the possibility of multiple bids, fair competition, the ability to monitor tenders and their results. We can say that the emergence of electronic public procurement has partially prevented all violations.